A high-toughness thermoplastic self-hardening furan resin and its preparation process

The high-toughness thermoplastic self-hardening furan resin addresses poor thermoplasticity and toughness in furan resin sand by using a composite curing agent and plasticizer, improving casting integrity and yield.

CN118652399BActive Publication Date: 2024-12-13YANCHENG HUAGANG FOUNDRY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410970845.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2024-12-13
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

Furan resin sand used in the foundry industry faces issues with poor thermoplasticity, toughness, and chemical resistance, leading to increased cracking in cast steel castings due to slow temperature changes and poor high-temperature penetration ability.

Method used

A high-toughness thermoplastic self-hardening furan resin is developed using a composite curing agent composed of 2-amino-4-hydroxy-6-ethylpyrimidine, 1,1'-carbonyldiimidazole, polyetheramine, and 4,4'-diaminodiphenyl disulfide, and a plasticizer made from ricinoleic acid, glutaric anhydride, and epichlorohydrin, along with glucose and acetone to enhance thermoplasticity and toughness.

Benefits of technology

The resin exhibits improved toughness, chemical resistance, and thermoplasticity, reducing cracking and enhancing mold yield by allowing smoother shrinkage during casting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-toughness thermoplastic self-hardening furan resin and a preparation process thereof, and belongs to the technical field of self-hardening furan resin preparation. The high-toughness thermoplastic self-hardening furan resin is composed of the following components in parts by weight: 24-42 parts of glucose, 2-4 parts of aluminum chloride, 1-4 parts of acetone, 2-3 parts of distilled water, 2-4 parts of composite curing agent, 30-55 parts of furfuryl alcohol, 1-5 parts of urea, 0.5-0.9 parts of silane, 0.1-0.3 parts of catalyst, 1-3 parts of plasticizer, wherein the composite curing agent is prepared from 2-amino-4-hydroxy-6-ethyl pyrimidine, 1,1'-carbonyldiimidazole, polyetheramine and 4,4'-diaminodiphenyl disulfide; the plasticizer is prepared from ricinoleic acid, glutaric anhydride and epichlorohydrin. The addition of composite curing agent and plasticizer can effectively increase the toughness, chemical resistance and thermoplasticity of self-hardening furan resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of self-hardening furan resin preparation, and in particular relates to a high-toughness thermoplastic self-hardening furan resin and a preparation process thereof. Background Art

[0002] In the foundry industry, resin sand is an important molding material, and its performance directly affects the quality and production efficiency of castings. Among them, furan resin sand, as a widely used type of resin sand, has significant advantages such as high core strength, easy recycling of old sand, and high dimensional accuracy of castings. However, with the continuous advancement of casting technology and the improvement of casting performance requirements, furan resin sand has also exposed some limitations in specific applications.

[0003] When furan resin sand is used to produce cast steel castings, the probability of cracks in the castings increases significantly. This is mainly due to the slow temperature change in the self-hardening furan resin sand core during casting, and the poor high-temperature penetration ability, which leads to poor overall yield of the mold. During the solidification and shrinkage process of the casting, the poor yield will hinder the shrinkage of the casting, thereby generating large shrinkage stress inside the casting, and ultimately leading to cracks. High-toughness thermoplastic self-hardening furan resin not only has the advantages of traditional furan resin sand, but also significantly improves the yield and high-temperature penetration ability of the mold by improving the thermoplasticity and easy disintegration of the material, so that the casting can shrink more smoothly during the solidification and shrinkage process, reducing the probability of cracks.

[0004] Patent CN 115850689 B discloses a formaldehyde-free self-hardening furan resin and its preparation method and application. The formaldehyde-free self-hardening furan resin is made of the following raw materials according to the mass ratio: 10-50% HAA, 0.35-0.7% silane coupling agent, 6-15% urea, 30-60% furfuryl alcohol and 0-20% methanol. HAA is a β-N hydroxyethyl compound. When HAA is used as a substitute for formaldehyde, the activity of its hydroxyl group is slightly weaker than that of the β-N hydroxymethyl compound generated by formaldehyde and urea. HAA is first condensed with urea to form a certain small molecule, and then copolymerized with furfuryl alcohol. Therefore, no free formaldehyde is generated in the preparation process or the finished product. The preparation process and product are safe and environmentally friendly. However, the thermoplasticity, toughness and chemical resistance of the furan resin prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a high-toughness thermoplastic self-hardening furan resin and a preparation process thereof, so as to solve the technical problems of poor thermoplasticity, toughness and poor chemical resistance of the self-hardening furan resin in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a high-toughness thermoplastic self-hardening furan resin, which is composed of the following components in parts by weight: 24-42 parts of glucose, 2-4 parts of aluminum chloride, 1-4 parts of acetone, 2-3 parts of distilled water, 2-4 parts of a composite curing agent, 30-55 parts of furfuryl alcohol, 1-5 parts of urea, 0.5-0.9 parts of silane, 0.1-0.3 parts of a catalyst, and 1-3 parts of a plasticizer, wherein the composite curing agent is prepared from 2-amino-4-hydroxy-6-ethylpyrimidine, 1,1'-carbonyldiimidazole, polyetheramine and 4,4'-diaminodiphenyl disulfide; and the plasticizer is prepared from ricinoleic acid, glutaric anhydride and epichlorohydrin.

[0008] Preferably, the preparation method of the composite curing agent comprises the following steps:

[0009] Q1: Under heating conditions, 2-amino-4-hydroxy-6-ethylpyrimidine and 1,1'-carbonyldiimidazole are dissolved in dimethyl sulfoxide respectively to obtain two solutions, and then the two solutions are mixed and stirred to produce a precipitate, which is then cooled, filtered, washed, and vacuum dried to obtain an intermediate product A;

[0010] Q2: The intermediate product A is mixed with the polyetheramine, and then reacted in a water bath. After the reaction is completed, the mixture is cooled, and n-hexane is placed in an ice-salt bath in a glass dish to control the temperature. The mixture is then added to the n-hexane and stirred to obtain an intermediate crude product B;

[0011] Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate the liquid again, repeat the operation, wash, dry, filter, rotary evaporate, and vacuum dry to obtain the intermediate product B;

[0012] Q4: Add the intermediate product B and 4,4'-diaminodiphenyl disulfide into a container. Under nitrogen protection, place the container in an oil bath for magnetic stirring. After complete mixing, cool the mixture to obtain a composite curing agent.

[0013] In the above process, 2-amino-4-hydroxy-6-ethylpyrimidine and 1,1'-carbonyldiimidazole undergo condensation reaction under heating and mixing conditions to generate intermediate product A, and then intermediate product A continues to undergo condensation reaction with polyetheramine, and the generation of side reactions is reduced at low temperature to obtain intermediate product B. After intermediate product B is mixed with 4,4'-diaminodiphenyl disulfide, a composite curing agent containing a flexible polyoxypropylene segment and a dynamic disulfide bond is obtained, wherein the synthesis reaction formula of the composite curing agent is as follows:

[0014]

[0015] Preferably, in Q1, the heating temperature is 80-85°C, the dosage ratio of 2-amino-4-hydroxy-6-ethylpyrimidine and dimethyl sulfoxide is (10-12) g: (300-360) mL, the dosage ratio of 1,1'-carbonyldiimidazole and dimethyl sulfoxide is (18-19) g: (100-106) mL, and the mass ratio of 2-amino-4-hydroxy-6-ethylpyrimidine and 1,1'-carbonyldiimidazole is (10-12): (1 8-19), the mixing and stirring temperature is 80-85°C, the time is 2-3h, and the washing process is washed with ethanol 3-5 times. The vacuum drying temperature is 30-40°C and the time is 1-2h. In Q2, the mass ratio of the intermediate product A to the polyetheramine is (13-15): (267-289), the water bath temperature is 40-45°C, the reaction time is 12-14h, the temperature control range is -10~-5°C, and the stirring time is 10-15min.

[0016] Preferably, in Q3, the operation is repeated 3-5 times, and after washing with saturated sodium chloride solution for 3-5 times, it is washed with distilled water for 1-2 times, and dried with anhydrous sodium sulfate. The rotary evaporation temperature is 40-50°C, the vacuum drying temperature is 28-30°C, and the time is 10-12h. In Q4, the mass ratio of the intermediate product B and 4,4'-diaminodiphenyl disulfide is (0.44-0.55): (0.396-0.495), the oil bath temperature is 80-90°C, and the stirring time is 10-20min.

[0017] Preferably, the catalyst comprises an alkaline catalyst and an acidic catalyst, wherein the alkaline catalyst is one or more combinations of sodium hydroxide, potassium hydroxide and sodium carbonate, and the acidic catalyst is one or more combinations of hydrochloric acid, sulfuric acid and acetic acid, and the mass ratio of the alkaline catalyst to the acidic catalyst is 3:2.

[0018] Preferably, the method for preparing the plasticizer comprises the following steps:

[0019] S1: Add ricinoleic acid, glutaric anhydride and tetrabutyl titanate into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, and heat and stir to react to obtain a plant-based dibasic acid;

[0020] S2: Add ricinoleic acid and epichlorohydrin into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, and heat and stir to react to obtain a plant-based diol;

[0021] S3: Add plant-based dibasic acid, plant-based diol and concentrated sulfuric acid into a container, heat and stir to react, and then cool to obtain a plasticizer.

[0022] In the above process, ricinoleic acid contains double bonds, carboxyl groups and hydroxyl groups. First, glutaric anhydride is used to react with it, and the hydroxyl groups in ricinoleic acid react with the carbonyl groups in glutaric anhydride to generate plant-based dibasic acid; then epichlorohydrin is used to react with ricinoleic acid, and the carboxyl groups in ricinoleic acid react with the epoxy groups in epichlorohydrin to generate plant-based diols. Subsequently, the acid and alcohol undergo esterification reaction to obtain a plasticizer, wherein the synthetic reaction equation of the plasticizer is as follows:

[0023]

[0024] Preferably, in S1, the molar ratio of ricinoleic acid, glutaric anhydride and tetrabutyl titanate is (0.8-1.1): (0.8-1.1): (0.004-0.006), the heating and stirring temperature is 110-130°C, and the reaction time is 3-5h; in S2, the molar ratio of ricinoleic acid and epichlorohydrin is (0.9-1.2): (0.9-1.2), the heating temperature is 110-130°C, and the reaction time is 2-4h; in S3, the molar ratio of plant-based dibasic acid, plant-based diol and concentrated sulfuric acid is (1-1.2): (1-1.2): (0.001-0.003), the heating and stirring temperature is 60-70°C, and the reaction time is 2-4h.

[0025] Preferably, a process for preparing a high-toughness thermoplastic self-hardening furan resin comprises the following steps:

[0026] Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating, setting a stirring speed, cooling, diluting, filtering and purifying after the stirring is completed, to obtain an aldehyde compound;

[0027] In the above process, aluminum chloride reacts with the hydroxyl groups on glucose to form a complex, activating the glucose molecules, followed by hydrogen transfer to form fructose molecules. Distilled water participates in hydrogen transfer to reduce the free energy barrier of intermolecular hydrogen transfer and accelerates the dehydration rate of fructose molecules. However, the presence of distilled water also promotes the degradation reaction. However, acetone inhibits the degradation of aldehyde compounds by preferentially solvating the active groups of aldehyde compounds, compensating for the disadvantages brought by distilled water. The synergistic effect of acetone and distilled water realizes the conversion of glucose to aldehyde compounds.

[0028] Step (2): adding an aldehyde compound, furfuryl alcohol and urea into a stainless steel reactor, heating for reaction, adding a catalyst and silane, cooling after the reaction, and then adding a composite curing agent and a plasticizer, stirring to mix them evenly, and after degassing, quickly pouring them into a polytetrafluoroethylene mold and placing them in a vacuum oven for curing to obtain a high-toughness thermoplastic self-hardening furan resin.

[0029] Preferably, in the step (1), the heating temperature is 150-170° C., the stirring speed is 1000-1200 rpm, the mixture is diluted with distilled water, and filtered with a 0.22 μm polyethersulfone filter.

[0030] Preferably, in step (2), the heating reaction temperature is 95-100°C, the reaction time is 30-45min, the temperature is lowered to 60-65°C, the stirring time is 10-15min, the degassing temperature is 80-90°C, the time is 20-30min, and the curing process is: curing at 110°C for 30min and curing at 170°C for 3h.

[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0032] 1. The present invention firstly uses 2-amino-4-hydroxy-6-ethylpyrimidine, 1,1'-carbonyldiimidazole, polyetheramine and 4,4'-diaminodiphenyl disulfide as raw materials to prepare a composite curing agent, then uses ricinoleic acid, glutaric anhydride and epichlorohydrin as raw materials to prepare a plasticizer, and then uses glucose as a raw material and acetone and distilled water as solvents to undergo a dehydration reaction to obtain aldehyde compounds, which are used to replace formaldehyde in the preparation process of self-hardening furan resin, thereby reducing the content of free formaldehyde in the production process, and the addition of the composite curing agent and the plasticizer can effectively improve the toughness, chemical resistance and thermoplasticity of the self-hardening furan resin.

[0033] 2. The present invention uses 2-amino-4-hydroxy-6-ethylpyrimidine, 1,1'-carbonyldiimidazole, polyetheramine and 4,4'-diaminodiphenyl disulfide as raw materials to prepare a composite curing agent. The composite curing agent is added to a self-hardening furan resin to effectively improve the curing speed, toughness and chemical resistance of the resin. The polyoxypropylene segment in the composite curing agent is a flexible segment, which can absorb and disperse external stress like a spring in the resin system to improve the toughness of the resin. The dynamic disulfide bonds in the resin can undergo reversible rupture and recombination. When the resin is impacted or stretched, energy is consumed by rupture and recombination of the disulfide bonds, further increasing the toughness. The dynamic disulfide bonds contained in the composite curing agent are chemically stable and can resist chemical corrosion. When the resin is exposed to a chemically corrosive environment, the dynamic disulfide bonds can maintain the integrity of its structure and enhance the chemical resistance of the resin. The addition of the composite curing agent can increase the crosslinking density of the resin, form a tighter molecular network structure, reduce pores and defects in the resin, and improve the chemical resistance of the self-hardening furan resin.

[0034] 3. The present invention uses ricinoleic acid, glutaric anhydride and epichlorohydrin as raw materials to prepare a plasticizer, which is added to a self-hardening furan resin to effectively improve its thermoplasticity. The plasticizer molecules are inserted into the long chains of the resin molecules, destroying the originally tightly stacked molecular chains, reducing the intermolecular forces, making the resin molecular chains easier to slide and move when subjected to thermal effects, thereby improving the thermoplasticity of the resin, and also increasing the free volume in the resin system. The movement space of the molecular chains becomes larger, which is beneficial to the movement of the molecular chains when heated, thereby improving the plasticity of the resin. In addition, the addition of the plasticizer can also reduce the glass transition temperature of the resin, thereby making the self-hardening furan resin have better thermoplasticity. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0036] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0037] Q1: Heat to 80°C, dissolve 11g of 2-amino-4-hydroxy-6-ethylpyrimidine and 18.5g of 1,1'-carbonyldiimidazole in 330mL and 103mL of dimethyl sulfoxide, respectively, to obtain two solutions, then mix and stir the two solutions, mix and stir at 85°C for 3h, a precipitate is generated, cool, filter, wash with ethanol 3 times, and vacuum dry at 40°C for 2h to obtain intermediate product A;

[0038] Q2: 14 g of intermediate product A was mixed with 278 g of polyetheramine, and then reacted in a water bath at 45°C for 12 h. After the reaction was completed, the mixture was cooled, and n-hexane was placed in an ice-salt bath in a glass dish to control the temperature to -8°C. The mixture was then added to n-hexane and stirred for 15 min to obtain an intermediate crude product B.

[0039] Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate it again, repeat the operation 5 times, wash it with saturated sodium chloride solution 3 times, wash it with distilled water once, dry it with anhydrous sodium sulfate, filter it, rotary evaporate it at 50°C, and vacuum dry it at 30°C for 12h to obtain the intermediate product B;

[0040] Q4: Add 0.50g of intermediate product B and 0.451g of 4,4'-diaminodiphenyl disulfide into a container. Under nitrogen protection, place the container in an 80°C oil bath and stir magnetically for 20 minutes. After complete mixing, cool and obtain a composite curing agent.

[0041] This embodiment discloses a method for preparing a plasticizer, comprising the following steps:

[0042] S1: 3.104 g of ricinoleic acid, 1.186 g of glutaric anhydride, and 0.018 g of tetrabutyl titanate were added to a container equipped with a thermometer and a stirring rod, and the stirrer and heating device were turned on. After heating and stirring at 130° C. for 5 h, a plant-based dibasic acid was obtained;

[0043] S2: 3.789 g of ricinoleic acid and 1.222 g of epichlorohydrin were added to a container equipped with a thermometer and a stirring rod, and the stirrer and the heating device were turned on. After heating and stirring at 110° C. for 4 hours, the plant-based diol was obtained;

[0044] S3: Add 4.383 g of plant-based dibasic acid, 4.643 g of plant-based diol and 0.002 g of concentrated sulfuric acid into a container, heat and stir at 70° C. for 4 h, and then cool to obtain a plasticizer.

[0045] The present embodiment discloses a high-toughness thermoplastic self-hardening furan resin, which is composed of the following components in parts by weight: 33 parts of glucose, 3 parts of aluminum chloride, 2.5 parts of acetone, 2.5 parts of distilled water, 3 parts of composite curing agent, 42.5 parts of furfuryl alcohol, 3 parts of urea, 0.7 parts of silane, 0.2 parts of catalyst, and 2 parts of plasticizer, wherein the catalyst is composed of sodium hydroxide and acetic acid, and the mass ratio of the two is 3:2.

[0046] This embodiment discloses a preparation process of a high-toughness thermoplastic self-hardening furan resin, comprising the following steps:

[0047] Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating at 170° C., setting the stirring speed to 1000 rpm, cooling after the stirring is completed, diluting with distilled water, filtering with a 0.22 μm polyethersulfone filter, and purifying to obtain an aldehyde compound;

[0048] Step (2): adding aldehyde compound, furfuryl alcohol and urea to a stainless steel reactor, heating at 100°C for reaction for 45 minutes, adding catalyst and silane, cooling to 60°C after the reaction, then adding composite curing agent and plasticizer, stirring for 15 minutes to make them evenly mixed, degassing at 90°C for 30 minutes, quickly pouring into a polytetrafluoroethylene mold and curing in a vacuum oven, the curing process is: curing at 110°C for 30 minutes, curing at 170°C for 3 hours, and obtaining a high-toughness thermoplastic self-hardening furan resin. Example

[0049] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0050] Q1: Heat to 80°C, dissolve 10g of 2-amino-4-hydroxy-6-ethylpyrimidine and 18g of 1,1'-carbonyldiimidazole in 300mL and 100mL of dimethyl sulfoxide, respectively, to obtain two solutions, then mix and stir the two solutions, mix and stir at 85°C for 3h, a precipitate is generated, cool, filter, wash with ethanol 3 times, and vacuum dry at 40°C for 2h to obtain intermediate product A;

[0051] Q2: 13 g of the intermediate product A was mixed with 267 g of polyetheramine, and then reacted in a water bath at 45°C for 12 h. After the reaction was completed, the mixture was cooled, and n-hexane was placed in an ice-salt bath in a glass dish to control the temperature to -8°C. The mixture was then added to n-hexane and stirred for 15 min to obtain an intermediate crude product B.

[0052] Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate it again, repeat the operation 5 times, wash it with saturated sodium chloride solution 3 times, wash it with distilled water once, dry it with anhydrous sodium sulfate, filter it, rotary evaporate it at 50°C, and vacuum dry it at 30°C for 12h to obtain the intermediate product B;

[0053] Q4: Add 0.44 g of intermediate product B and 0.396 g of 4,4'-diaminodiphenyl disulfide into a container. Under nitrogen protection, place the container in an 80°C oil bath and stir magnetically for 20 minutes. After complete mixing, cool and obtain a composite curing agent.

[0054] This embodiment discloses a method for preparing a plasticizer, comprising the following steps:

[0055] S1: 2.614 g of ricinoleic acid, 1 g of glutaric anhydride, and 0.015 g of tetrabutyl titanate were added to a container equipped with a thermometer and a stirring rod, and the stirrer and heating device were turned on. After heating and stirring at 130° C. for 5 h, a plant-based dibasic acid was obtained;

[0056] S2: Add 3.239 g of ricinoleic acid and 1 g of epichlorohydrin into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, heat and stir at 110° C. for 4 h to obtain a plant-based diol;

[0057] S3: Add 3.985 g of plant-based dibasic acid, 4.204 g of plant-based diol and 0.001 g of concentrated sulfuric acid into a container, heat and stir at 70° C. for 4 h, and then cool to obtain a plasticizer.

[0058] The present embodiment discloses a high-toughness thermoplastic self-hardening furan resin, which is composed of the following ingredients in parts by weight: 24 parts of glucose, 2 parts of aluminum chloride, 1 part of acetone, 2 parts of distilled water, 2 parts of composite curing agent, 30 parts of furfuryl alcohol, 1 part of urea, 0.5 parts of silane, 0.1 parts of catalyst, and 1 part of plasticizer, wherein the catalyst is composed of sodium hydroxide and acetic acid, and the mass ratio of the two is 3:2.

[0059] This embodiment discloses a preparation process of a high-toughness thermoplastic self-hardening furan resin, comprising the following steps:

[0060] Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating at 170° C., setting the stirring speed to 1000 rpm, cooling after the stirring is completed, diluting with distilled water, filtering with a 0.22 μm polyethersulfone filter, and purifying to obtain an aldehyde compound;

[0061] Step (2): adding aldehyde compound, furfuryl alcohol and urea to a stainless steel reactor, heating at 100°C for reaction for 45 minutes, adding catalyst and silane, cooling to 60°C after the reaction, then adding composite curing agent and plasticizer, stirring for 15 minutes to make them evenly mixed, degassing at 90°C for 30 minutes, quickly pouring into a polytetrafluoroethylene mold and curing in a vacuum oven, the curing process is: curing at 110°C for 30 minutes, curing at 170°C for 3 hours, and obtaining a high-toughness thermoplastic self-hardening furan resin. Example

[0062] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0063] Q1: Heat to 80°C, dissolve 12g of 2-amino-4-hydroxy-6-ethylpyrimidine and 19g of 1,1'-carbonyldiimidazole in 360mL and 106mL of dimethyl sulfoxide, respectively, to obtain two solutions, then mix and stir the two solutions, mix and stir at 85°C for 3h, a precipitate is generated, cool, filter, wash with ethanol 3 times, and vacuum dry at 40°C for 2h to obtain intermediate product A;

[0064] Q2: 15 g of the intermediate product A was mixed with 289 g of polyetheramine, and then reacted in a water bath at 45°C for 12 h. After the reaction was completed, the mixture was cooled, and n-hexane was placed in an ice-salt bath in a glass dish to control the temperature to -8°C. The mixture was then added to n-hexane and stirred for 15 min to obtain an intermediate crude product B.

[0065] Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate it again, repeat the operation 5 times, wash it with saturated sodium chloride solution 3 times, wash it with distilled water once, dry it with anhydrous sodium sulfate, filter it, rotary evaporate it at 50°C, and vacuum dry it at 30°C for 12h to obtain the intermediate product B;

[0066] Q4: Add 0.55g of intermediate product B and 0.495g of 4,4'-diaminodiphenyl disulfide into a container. Under nitrogen protection, place the container in an 80°C oil bath and stir it magnetically for 20 minutes. After complete mixing, cool it to obtain a composite curing agent.

[0067] This embodiment discloses a method for preparing a plasticizer, comprising the following steps:

[0068] S1: 3.594 g of ricinoleic acid, 1.375 g of glutaric anhydride, and 0.022 g of tetrabutyl titanate were added to a container equipped with a thermometer and a stirring rod, and the stirrer and heating device were turned on. After heating and stirring at 130° C. for 5 h, a plant-based dibasic acid was obtained;

[0069] S2: Add 4.319 g of ricinoleic acid and 1.333 g of epichlorohydrin into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, heat and stir at 110° C. for 4 hours to obtain a plant-based diol;

[0070] S3: Add 4.782 g of plant-based dibasic acid, 5.045 g of plant-based diol and 0.003 g of concentrated sulfuric acid into a container, heat and stir at 70° C. for 4 h, and then cool to obtain a plasticizer.

[0071] The present embodiment discloses a high-toughness thermoplastic self-hardening furan resin, which is composed of the following components in parts by weight: 42 parts of glucose, 4 parts of aluminum chloride, 4 parts of acetone, 3 parts of distilled water, 4 parts of a composite curing agent, 55 parts of furfuryl alcohol, 5 parts of urea, 0.9 parts of silane, 0.3 parts of a catalyst, and 3 parts of a plasticizer, wherein the catalyst is composed of sodium hydroxide and acetic acid, and the mass ratio of the two is 3:2.

[0072] This embodiment discloses a preparation process of a high-toughness thermoplastic self-hardening furan resin, comprising the following steps:

[0073] Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating at 170° C., setting the stirring speed to 1000 rpm, cooling after the stirring is completed, diluting with distilled water, filtering with a 0.22 μm polyethersulfone filter, and purifying to obtain an aldehyde compound;

[0074] Step (2): adding aldehyde compound, furfuryl alcohol and urea to a stainless steel reactor, heating at 100°C for reaction for 45 minutes, adding catalyst and silane, cooling to 60°C after the reaction, then adding composite curing agent and plasticizer, stirring for 15 minutes to make them evenly mixed, degassing at 90°C for 30 minutes, quickly pouring into a polytetrafluoroethylene mold and curing in a vacuum oven, the curing process is: curing at 110°C for 30 minutes, curing at 170°C for 3 hours, and obtaining a high-toughness thermoplastic self-hardening furan resin. Example

[0075] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0076] Q1: Heat to 80°C, dissolve 10.5 g of 2-amino-4-hydroxy-6-ethylpyrimidine and 18.2 g of 1,1'-carbonyldiimidazole in 320 mL and 102 mL of dimethyl sulfoxide, respectively, to obtain two solutions, then mix and stir the two solutions, mix and stir at 85°C for 3 h, a precipitate is generated, cool, filter, wash with ethanol 3 times, and vacuum dry at 40°C for 2 h to obtain intermediate product A;

[0077] Q2: 13.5 g of the intermediate product A was mixed with 271 g of polyetheramine, and then reacted in a water bath at 45°C for 12 h. After the reaction was completed, the mixture was cooled, and n-hexane was placed in an ice-salt bath in a glass dish to control the temperature to -8°C. The mixture was then added to n-hexane and stirred for 15 min to obtain an intermediate crude product B.

[0078] Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate it again, repeat the operation 5 times, wash it with saturated sodium chloride solution 3 times, wash it with distilled water once, dry it with anhydrous sodium sulfate, filter it, rotary evaporate it at 50°C, and vacuum dry it at 30°C for 12h to obtain the intermediate product B;

[0079] Q4: Add 0.48g of intermediate product B and 0.407g of 4,4'-diaminodiphenyl disulfide into a container. Under nitrogen protection, place the container in an 80°C oil bath and stir magnetically for 20 minutes. After complete mixing, cool and obtain a composite curing agent.

[0080] This embodiment discloses a method for preparing a plasticizer, comprising the following steps:

[0081] S1: 3.274 g of ricinoleic acid, 1.213 g of glutaric anhydride, and 0.016 g of tetrabutyl titanate were added to a container equipped with a thermometer and a stirring rod, and the stirrer and heating device were turned on. After heating and stirring at 130° C. for 5 h, a plant-based dibasic acid was obtained;

[0082] S2: Add 3.473 g of ricinoleic acid and 1.019 g of epichlorohydrin into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, heat and stir at 110° C. for 4 h to obtain a plant-based diol;

[0083] S3: Add 4.021 g of plant-based dibasic acid, 4.417 g of plant-based diol and 0.0015 g of concentrated sulfuric acid into a container, heat and stir at 70° C. for 4 h, and then cool to obtain a plasticizer.

[0084] The present embodiment discloses a high-toughness thermoplastic self-hardening furan resin, which is composed of the following ingredients in parts by weight: 28 parts of glucose, 2.5 parts of aluminum chloride, 2 parts of acetone, 2.3 parts of distilled water, 2.5 parts of a composite curing agent, 35 parts of furfuryl alcohol, 2 parts of urea, 0.6 parts of silane, 0.25 parts of a catalyst, and 2.5 parts of a plasticizer, wherein the catalyst is composed of sodium hydroxide and acetic acid, and the mass ratio of the two is 3:2.

[0085] This embodiment discloses a preparation process of a high-toughness thermoplastic self-hardening furan resin, comprising the following steps:

[0086] Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating at 170° C., setting the stirring speed to 1000 rpm, cooling after the stirring is completed, diluting with distilled water, filtering with a 0.22 μm polyethersulfone filter, and purifying to obtain an aldehyde compound;

[0087] Step (2): adding aldehyde compound, furfuryl alcohol and urea to a stainless steel reactor, heating at 100°C for reaction for 45 minutes, adding catalyst and silane, cooling to 60°C after the reaction, then adding composite curing agent and plasticizer, stirring for 15 minutes to make them evenly mixed, degassing at 90°C for 30 minutes, quickly pouring into a polytetrafluoroethylene mold and curing in a vacuum oven, the curing process is: curing at 110°C for 30 minutes, curing at 170°C for 3 hours, and obtaining a high-toughness thermoplastic self-hardening furan resin.

[0088] Comparative Example 1

[0089] Comparative Example 1 Compared with Example 1, in the process of preparing the composite curing agent in Comparative Example 1, no 2-amino-4-hydroxy-6-ethylpyrimidine was added, and other conditions remained unchanged.

[0090] Comparative Example 2

[0091] Comparative Example 2 Compared with Example 1, in the process of preparing the composite curing agent in Comparative Example 2, no polyetheramine was added, and other conditions remained unchanged.

[0092] Comparative Example 3

[0093] Comparative Example 3 Compared with Example 1, in the process of preparing the composite curing agent in Comparative Example 3, 4,4'-diaminodiphenyl disulfide was not added, and other conditions remained unchanged.

[0094] Comparative Example 4

[0095] Comparative Example 4 Compared with Example 1, in the process of preparing the plasticizer in Comparative Example 4, glutaric anhydride was not added, and other conditions remained unchanged.

[0096] Comparative Example 5

[0097] Comparative Example 5 Compared with Example 1, in the process of preparing the plasticizer in Comparative Example 5, epichlorohydrin is not added, and other conditions remain unchanged.

[0098] Comparative Example 6

[0099] Comparative Example 6 Compared with Example 1, in the process of preparing the high-toughness thermoplastic self-hardening furan resin in Comparative Example 6, no composite curing agent is added, and other conditions remain unchanged.

[0100] Comparative Example 7

[0101] Comparative Example 7 Compared with Example 1, in the process of preparing the high-toughness thermoplastic self-hardening furan resin in Comparative Example 7, no plasticizer is added, and other conditions remain unchanged.

[0102] Comparative Example 8

[0103] Comparative Example 8 Compared with Example 1, in the process of preparing the high-toughness thermoplastic self-hardening furan resin in Comparative Example 8, formaldehyde is used instead of the aldehyde compound, and other conditions remain unchanged.

[0104] The samples prepared in Examples 1-4 and Comparative Examples 1-8 were subjected to performance tests. The free formaldehyde content in the samples was tested according to the standard JB / T 7526-2008, the toughness of the samples was tested according to the standard GB / T 1451-2005, the thermoplasticity of the samples was tested according to the standard ASTM D648, and the chemical resistance of the samples was tested according to the standard QB / T 3826-1999. The test results are shown in Table 1:

[0105] Table 1

[0106]

[0107] From the test results in Table 1, it can be seen that the high-toughness thermoplastic self-hardening furan resin prepared in Examples 1-4 of the present invention has excellent chemical resistance, thermoplasticity, toughness and low free formaldehyde content. From the comparison between Comparative Example 1 and Examples 1-4, it can be seen that the addition of 2-amino-4-hydroxy-6-ethylpyrimidine can effectively improve the chemical resistance and toughness of the thermoplastic self-hardening furan resin; from the comparison between Comparative Example 2 and Examples 1-4, it can be seen that the addition of polyetheramine can effectively improve the chemical resistance and toughness of the thermoplastic self-hardening furan resin; from the comparison between Comparative Example 3 and Examples 1-4, it can be seen that the addition of 4,4'-diaminodiphenyl disulfide can effectively improve the chemical resistance and toughness of the thermoplastic self-hardening furan resin; from the comparison between Comparative Example 4 and Examples 1-4, it can be seen that the addition of glutaric anhydride can effectively improve the thermoplastic self-hardening furan resin. Thermoplasticity of hard furan resin; By comparing Comparative Example 5 with Examples 1-4, it can be seen that the addition of epichlorohydrin can effectively improve the thermoplasticity of thermoplastic self-hardening furan resin; By comparing Comparative Example 6 with Examples 1-4, it can be seen that the addition of a composite curing agent can effectively improve the chemical resistance and toughness of the thermoplastic self-hardening furan resin; By comparing Comparative Example 7 with Examples 1-4, it can be seen that the addition of a plasticizer can effectively improve the thermoplasticity of the thermoplastic self-hardening furan resin; By comparing Comparative Example 8 with Examples 1-4, it can be seen that the use of aldehyde compounds instead of formaldehyde can effectively reduce the free formaldehyde content in the thermoplastic self-hardening furan resin.

[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high toughness thermoplastic self-hardening furan resin, It is characterized in that The invention is composed of the following components in parts by weight: 24-42 parts of glucose, 2-4 parts of aluminum chloride, 1-4 parts of acetone, 2-3 parts of distilled water, 2-4 parts of composite curing agent, 30-55 parts of furfuryl alcohol, 1-5 parts of urea, 0.5-0.9 parts of silane, 0.1-0.3 parts of catalyst, and 1-3 parts of plasticizer, wherein the composite curing agent is prepared from 2-amino-4-hydroxy-6-ethylpyrimidine, 1,1'-carbonyldiimidazole, polyetheramine and 4,4'-diaminodiphenyl disulfide; and the plasticizer is prepared from ricinoleic acid, glutaric anhydride and epichlorohydrin; The preparation method of the composite curing agent comprises the following steps: Q1: Under heating conditions, 2-amino-4-hydroxy-6-ethylpyrimidine and 1,1'-carbonyldiimidazole are dissolved in dimethyl sulfoxide respectively to obtain two solutions, and then the two solutions are mixed and stirred to produce a precipitate, which is then cooled, filtered, washed, and vacuum dried to obtain an intermediate product A; Q2: The intermediate product A is mixed with the polyetheramine, and then reacted in a water bath. After the reaction is completed, the mixture is cooled, and n-hexane is placed in an ice-salt bath in a glass dish to control the temperature. The mixture is then added to the n-hexane and stirred to obtain an intermediate crude product B; Q3: Pour the intermediate crude product B into a separatory funnel, separate the lower layer of oily liquid, then dissolve it with dichloromethane, separate the liquid again, repeat the operation, wash, dry, filter, rotary evaporate, and vacuum dry to obtain the intermediate product B; Q4: Add the intermediate product B and 4,4'-diaminodiphenyl disulfide into the container. Under nitrogen protection, place the container in an oil bath for magnetic stirring. After complete mixing, cool it to obtain a composite curing agent. The preparation method of the plasticizer comprises the following steps: S1: Add ricinoleic acid, glutaric anhydride and tetrabutyl titanate into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, and heat and stir to react to obtain a plant-based dibasic acid; S2: Add ricinoleic acid and epichlorohydrin into a container equipped with a thermometer and a stirring rod, turn on the stirrer and the heating device, and heat and stir to react to obtain a plant-based diol; S3: Add plant-based dibasic acid, plant-based diol and concentrated sulfuric acid into a container, heat and stir to react, and then cool to obtain a plasticizer.

2. The high-toughness thermoplastic self-hardening furan resin according to claim 1, It is characterized in that In the Q1, the heating temperature is 80-85°C, the amount ratio of 2-amino-4-hydroxy-6-ethylpyrimidine and dimethyl sulfoxide is (10-12) g: (300-360) mL, the amount ratio of 1,1'-carbonyldiimidazole and dimethyl sulfoxide is (18-19) g: (100-106) mL, and the mass ratio of 2-amino-4-hydroxy-6-ethylpyrimidine and 1,1'-carbonyldiimidazole is (10-12): (18- 19), the mixing and stirring temperature is 80-85°C, the time is 2-3h, the washing process is washed with ethanol 3-5 times, the vacuum drying temperature is 30-40°C, and the time is 1-2h; in Q2, the mass ratio of the intermediate product A to the polyetheramine is (13-15): (267-289), the water bath temperature is 40-45°C, the reaction time is 12-14h, the temperature control range is -10~-5°C, and the stirring time is 10-15min.

3. The high-toughness thermoplastic self-hardening furan resin according to claim 1, It is characterized in that In the Q3, the operation is repeated 3-5 times, and the mixture is washed with a saturated sodium chloride solution for 3-5 times, then washed with distilled water for 1-2 times, and dried with anhydrous sodium sulfate. The rotary evaporation temperature is 40-50°C, the vacuum drying temperature is 28-30°C, and the time is 10-12h. In the Q4, the mass ratio of the intermediate product B and 4,4'-diaminodiphenyl disulfide is (0.44-0.55): (0.396-0.495), the oil bath temperature is 80-90°C, and the stirring time is 10-20min.

4. The high-toughness thermoplastic self-hardening furan resin according to claim 1, It is characterized in that The catalyst includes an alkaline catalyst and an acidic catalyst, wherein the alkaline catalyst is one or more combinations of sodium hydroxide, potassium hydroxide and sodium carbonate, the acidic catalyst is one or more combinations of hydrochloric acid, sulfuric acid and acetic acid, and the mass ratio of the alkaline catalyst to the acidic catalyst is 3:

2.

5. The high-toughness thermoplastic self-hardening furan resin according to claim 1, It is characterized in that In S1, the molar ratio of ricinoleic acid, glutaric anhydride and tetrabutyl titanate is (0.8-1.1): (0.8-1.1): (0.004-0.006), the heating and stirring temperature is 110-130°C, and the reaction time is 3-5h; in S2, the molar ratio of ricinoleic acid and epichlorohydrin is (0.9-1.2): (0.9-1.2), the heating temperature is 110-130°C, and the reaction time is 2-4h; in S3, the molar ratio of plant-based dibasic acid, plant-based diol and concentrated sulfuric acid is (1-1.2): (1-1.2): (0.001-0.003), the heating and stirring temperature is 60-70°C, and the reaction time is 2-4h.

6. A process for preparing the high-toughness thermoplastic self-hardening furan resin according to any one of claims 1 to 5, It is characterized in that The following steps are involved: Step (1): adding glucose, aluminum chloride, acetone and distilled water to a polytetrafluoroethylene liner containing a stirrer, placing the liner in a stainless steel reactor, placing the stainless steel reactor in a heating device, heating, setting a stirring speed, cooling, diluting, filtering and purifying after the stirring is completed, to obtain an aldehyde compound; Step (2): adding an aldehyde compound, furfuryl alcohol and urea into a stainless steel reactor, heating for reaction, adding a catalyst and silane, cooling after the reaction, and then adding a composite curing agent and a plasticizer, stirring to mix them evenly, and after degassing, quickly pouring them into a polytetrafluoroethylene mold and placing them in a vacuum oven for curing to obtain a high-toughness thermoplastic self-hardening furan resin.

7. A process for preparing a high-toughness thermoplastic self-hardening furan resin according to claim 6, It is characterized in that In the step (1), the heating temperature is 150-170° C., the stirring speed is 1000-1200 rpm, the mixture is diluted with distilled water, and filtered with a 0.22 μm polyethersulfone filter.

8. A process for preparing a high-toughness thermoplastic self-hardening furan resin according to claim 6, It is characterized in that In the step (2), the heating reaction temperature is 95-100°C, the reaction time is 30-45 minutes, the temperature is lowered to 60-65°C, the stirring time is 10-15 minutes, the degassing temperature is 80-90°C, the time is 20-30 minutes, and the curing process is: curing at 110°C for 30 minutes and curing at 170°C for 3 hours.